2007
DOI: 10.1016/j.ijgo.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum corticotropin‐releasing hormone and ACTH levels as predictive markers of premature labor

Abstract: CRH and ACTH serum levels in women diagnosed with preterm labor could be used as predictors for the timing of parturition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…The synergistic stimulation of the feto-placental unit and the pituitary adrenal axis of both fetus and mother play a pivotal role in initiation of parturition [4,5]. Our study is in accordance with Makrigiannakis et al who demonstrated the role of serum ACTH levels as predictive marker for premature labor [6]. Ferritin, an iron storage protein, is an acute phase reactant.…”
Section: Discussionsupporting
confidence: 92%
“…The synergistic stimulation of the feto-placental unit and the pituitary adrenal axis of both fetus and mother play a pivotal role in initiation of parturition [4,5]. Our study is in accordance with Makrigiannakis et al who demonstrated the role of serum ACTH levels as predictive marker for premature labor [6]. Ferritin, an iron storage protein, is an acute phase reactant.…”
Section: Discussionsupporting
confidence: 92%
“…42 Other studies have found associations between stress hormones (i.e., cortisol and adrenocorticotrophin-releasing hormone) and PTB, though IPV as a stressor was not specifically measured. [43][44][45] These findings highlight the need for further research on the neuroendocrine changes evident in pregnant women experiencing IPV. An enhanced understanding of the links between violence, HPA activation, utero-placental perfusion, and adverse neonatal outcomes may provide an important pathway to reducing disparities in neonatal outcomes.…”
Section: Severity Of Violence and Adverse Neonatal Outcomesmentioning
confidence: 89%
“…At the physiological level, it is clear that many factors are involved in the onset of labor, including hormonal metabolism and structural changes to the uterus and myometrium (Petraglia et al, 1996) but the effects and interactions among these factors are not fully understood (Challis, 1994). Research from our group Sandman et al, 2006;Sandman et al, 1995Sandman et al, , 1999bWadhwa et al, 1996;Wadhwa et al, 2004;Wadhwa et al, 1998) and many others (Braastad, 1998;Lindsay & Nieman, 2005;Makrigiannakis et al, 2007;Neumann et al, 1998) indicates that a primary pathway of the effects of stress on the human fetus is the HPA stress axis. This review will focus on the role that stress plays in determining preterm birth.…”
mentioning
confidence: 91%